A New Fe(III) Complex Derived from Cyclohexane Based Imine Derivative: Studies on H2PO4− Recognition and Anti‐Cancer Activity Against MCF7 and MDA‐MB‐231 Human Breast Cancer Cells. Issue 5 (1st February 2023) - Taniya, Seikh; Khanra, Somnath; Bhowmik, Arpan Dey; Bandyopadhyay, Arindam; Chatterjee, Sudeshna; Chattopadhyay, Ansuman; Das, Debasis
Abstract: An imine derivative, N, N′‐bis‐(2‐hydroxo‐3‐ethoxy‐benzylidene)‐cyclohexane‐1, 2‐diamine have been explored for the synthesis of a new Fe(III) complex (F3), the structure of which is confirmed by single crystal X‐Ray diffraction ( SC‐XRD) analysis. The F3 is very sensitive for selective optical recognition of H2 PO4 − in DMSO/H2 O (4/1, v/v) media. The interaction of F3 with H2 PO4 − allows nano‐molar (91.17 nM) level detection of H2 PO4 − having association constant, 6.92×10 4 M −1 . In addition, F3 is found to have an efficient anti‐cancer activity against human breast cancer cell line MCF7 and MDA‐MB‐231. Abstract : Bis‐imine derived Fe(III) complex ( F3), structurally characterized by single crystal X‐ray, optically recognises H2 PO4 − in DMSO(4/1, v/v) media. The interaction of F3 with H2 PO4 − allows nano‐molar (91.17 nM) level detection of H2 PO4 − having a binding constant of 6.92×10 4 M − . Moreover, F3 displays effective anti‐cancer activity on cell apoptosis.